The Effectiveness of Motor Vehicle E-SAMSAT Services (A Research Study at the Badung Regency SAMSAT Office) - Eka, I Gede Agus Eka Pradnyana; I Wayan Astawa; Sri Sulandari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Taxes are the main source of state revenue and play a crucial role in funding development and providing public services. In Indonesia, one significant type of tax that contributes to regional revenue is the Motor Vehicle Tax (PKB). The government continuously strives to improve taxpayer compliance through technology-based public service innovations, one of which is the E-Samsat service. This service aims to simplify the process of paying motor vehicle taxes online in order to increase efficiency and public participation. This study employs a qualitative research method with a descriptive approach, aiming to gain a deeper understanding of social phenomena occurring in natural settings. As such, the study presents new insights, particularly by identifying several key aspects related to the Effectiveness of E-Samsat Services for Motor Vehicles in Badung Regency, including (1) Goal Achievement, (2) Adaptation, and (3) Integrity. The objective of this research is to analyze the role of the E-Samsat service in improving motor vehicle taxpayer compliance in Badung Regency, as well as to identify the challenges faced by the public in using this service. The results of the analysis are expected to provide strategic recommendations for local governments to optimize the use of technology in order to improve tax compliance and achieve regional revenue targets. Factors influencing the effectiveness of the E-Samsat service in the Badung Regency Samsat Office include the public's willingness to change old habits into new ones. These habits refer to the continued use of third-party agents (biro samsat) to handle vehicle tax payments, and the tendency of many people to still come directly to the Samsat office to pay their motor vehicle taxes. Keywords: Motor Vehicle Tax, E-Samsat, Taxpayer Compliance, Public Service, Badung Regency